The Implementation of Distance Learning Policy During the Covid-19 Pandemic - Tedja, Jeanne Noveline (Department of Sociology, Universitas Nasional (Indonesia), 2020)
The impact of the Pandemic Covid 19 is felt almost everywhere in the world, including Indonesia. Almost all sectors of life receive and feel the negative impact of the existence of this pandemic, not only the health sector but also the economic sector, education, even religion and worship activities. In the education sector, to break the chain of virus transmission, the Government imposes social restrictions including PJJ (Distance Learning) policy for all students at all levels of education from kindergarten to high school / vocational school. PJJ is conducted online at each home using computer facilities, laptops or smartphones with special applications. This policy is proof that the Government continues to fulfill children's education rights in the midst of a pandemic. In its implementation, PJJ invites various reactions especially from students. Various complaints began to emerge after PJJ was running for a week. Of the 213 complaints reports submitted to the Indonesian Child Protection Commission (KPAI), the majority of complaints are related to the severity of the assignments given by teachers to students and regarding PJJ that drains energy and internet quota. In addition, the limitations of online learning facilities, become obstacles for students in joining PJJ. This complaint report was confirmed by a survey of 1700 students conducted by KPAI. In another survey conducted by KPAI with FSGI, it was found that the inability and unpreparedness of online teaching teachers was another problem in PJJ. Policy implementation is a crucial stage in the policy process. No matter how good a policy is, it will not succeed if it is not implemented according to plan. This research, which uses a qualitative approach and content analysis method, aims to analyze the implementation of PJJ policies for students during the Covid 19 pandemic. The research is expected to be able to define social reality and provide theory, data, and analysis that can be utilized by the Government in developing education policies in emergencies.Keywords : Policy implementation, children, covid 19, education, PJJ.